Advanced practical organic chemistry - Leonard, J. (Blackie, 1990)
Any research which uses new organic chemicals or those which are not available commercially will at some time require the synthesis of such compounds. This practical book covers the most up-to-date techniques commonly used in organic synthesis, and updates the first edition. This book should be of interest to: postgraduate industrial and advanced undergraduate organic chemists; biologists, biochemists and genetic engineers; material scientists; polymer researchers; and pharmaceutical, agrochemical and others involved with fine chemicals research and electronics.